Chapter Chiese e cappelle dello spazio signorile - Curzel, Emanuele (Reti Medievali E-Book, 2023)
The purpose of the essay is to illustrate the role of territorial ecclesiastical institutions in the organization of the Trentino lordships of the fourteenth and fifteenth centuries. From a de facto hegemony and control, sometimes exercised by force, we generally pass to forms of patronage endorsed by the bishop, especially between the fifteenth and sixteenth centuries. There are also chapels located inside the castle.